The Impact of the Increase in Fuel Prices on Public Welfare and Nine Staple Materials in Gedung Johor Village, Medan Johor District, Medan City - Adhani, Nadia; Syafii, M. (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
Research purposes This done For know Impact Increase in Fuel Oil (BBM) against welfare society and nine aterial The main point in Medan Johor District, Gedung Johor Village, Medan City. Types of research This is study qualitative. Population and sample study This is poor people Family Program ministry of hope (PKH) social in Medan Johor District, Gedung Johor Village, Medan City as many as 390 people. The sampling technique sample in study This is Probability Sampling technique with use formula slovin so that sample there were 80 respondents. Data collection techniques in study This is with spread questionnaire. Data analysis methods using different and descriptive tests qualitative. The returned questionnaire totaling 80 questionnaires. The results of the study show that Ascension Fuel prices (BBM) have an impact positive to increase Price of Nine Ingredients main matter This seen increase price material burn oil impact the rise Price of Nine Ingredients principal. Increase Fuel prices (BBM) have an impact negative to welfare public matter This show that the increase in fuel oil (BBM) can increase expenditure society and reduce welfare public.